2021
DOI: 10.12890/2021_002409
|View full text |Cite
|
Sign up to set email alerts
|

Marantic Endocarditis Associated with COVID-19: A Rare Case Report of a Potentially Deadly Disease

Abstract: Coronavirus disease 2019 (COVID-19) has overwhelmed healthcare globally with millions of cases and over 2 million deaths worldwide. The hypercoagulable state associated with COVID-19 is a well-recognized complication that carries a poor prognosis. Marantic endocarditis, or non-bacterial thrombotic endocarditis (NBTE), is caused by a sterile vegetation on the cardiac valves resulting from the deposition of fibrin and platelet aggregates. It is highly associated with the hypercoagulable and acquired inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Notably, it has been suggested that COVID-19 infection can induce hypercoagulation, potentially contributing to pulmonary embolism, deep venous thrombosis, and the development of NBTE [7,8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been suggested that COVID-19 infection can induce hypercoagulation, potentially contributing to pulmonary embolism, deep venous thrombosis, and the development of NBTE [7,8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Apixaban is not approved by FDA for arterial thrombosis/thromboembolic or left ventricular thrombus. Although apixaban was successfully used for the treatment of NBTE in a recent COVID-19 NBTE case report 13. Excision of the vegetation may have a role in some patients who do not have advanced malignancy 14.…”
Section: Discussionmentioning
confidence: 99%
“…Although apixaban was successfully used for the treatment of NBTE in a recent COVID-19 NBTE case report. 13 Excision of the vegetation may have a role in some patients who do not have advanced malignancy. 14 Lifelong anticoagulation is usually recommended in patients with cancer due to the reported recurrence of NBTE in patients taken off anticoagulation.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…In the context of COVID-19 infection, it is important to be mindful of other differentials such as marantic endocarditis or non-bacterial thrombotic endocarditis. 11 COVID-19 infection causes a pro-inflammatory state with cytokine storm, which contributes to local tissue destruction and resultant thrombus vegetation formation on the disrupted areas. In the context of negative blood culture results, marantic endocarditis must be considered in a patient with COVID-19 infection as it is responsive to anticoagulants.…”
Section: Discussionmentioning
confidence: 99%